Arterial thromboembolism of non-cardiogenic origin in a domestic feline with ischemia and reperfusion syndrome - a case report - Schaefer, Gabriela da Cruz; Veronezi, Tayná Mayer; Luz, Camila Gonçalves da; Gutierrez, Letícia Gutierrez de; Scherer, Simone; Pavarini, Saulo Petinatti; Costa, Fernanda Vieira Amorim da (Semina: Ciências Agrárias, 2020)
Arterial thromboembolism (ATE) is an acute and severe clinical condition resulting from the formation of a thrombus and its accommodation in an artery, impairing the perfusion of tissues irrigated by it. In felines, it is often related to hypertrophic cardiomyopathy, but there are reports of its association with neoplasms. Ischemia and reperfusion syndrome may occur secondary to ATE and result in difficult to correct electrolyte and acid-base imbalances. The aim of the present study is to describe a case of ATE, including its clinical and laboratory findings and electrolyte and acid-base changes compatible with ischemia and reperfusion syndrome. A 14-year-old crossbreed female feline with sudden pelvic limb paralysis was treated at the Feline Medicine Service of the Federal University of Rio Grande do Sul. Clinical and laboratory alterations included hypothermia, hypotension, bradycardia, azotemia, metabolic acidosis, and hyperkalemia. The electrocardiogram indicated sinoventricular rhythm, and echocardiogram evaluation showed no alterations. Thorax radiographic evaluation revealed areas of higher radiopacity in the pulmonary fields. We opted for abdominal aorta arteriotomy as an emergency treatment for thrombus removal. The feline died in the postoperative period, and histopathological examination of lungs, mediastinal lymph nodes, and heart were performed, being compatible with pulmonary adenocarcinoma with lymph node metastasis. This study deals with a case of ATE of possible neoplastic origin, which is uncommon in cats. In this case, the patient had difficult-to-manage hemodynamic impairment, as well as electrolyte and acid-base balance disorders severe and refractory to therapy, culminating in death. The time to start treatment from the presentation of clinical signs may be determinant in therapeutic success, reducing the possible effects of reperfusion syndrome.